The effects of alpha-lipoic acid on MMP-2 and MMP-9 activities in a rat renal ischemia and re-perfusion model. (May 2014) - Cavdar, Z; Ozbal, S; Celik, A; Ergur, BU; Guneli, E; Ural, C; Camsari, T; Guner, GA
Abstract Matrix metalloproteinases (MMPs) are enzymes that are responsible for degradation of extracellular matrix (ECM); they are involved in the pathogenesis of ischemia-re-perfusion (I-R) injury. We investigated the possible preventive effect of alpha-lipoic acid (LA) in a renal I-R injury model in rats by assessing its reducing effect on the expression and activation of MMP-2 and MMP-9 induced by I-R. Rats were assigned to four groups: control, sham-operated, I-R (saline, i.p.) and I-R+ LA (100 mg/kg, i.p.). After a right nephrectomy, I-R was induced by clamping the left renal pedicle for 1 h, followed by 6 h re-perfusion. In the sham group, a right nephrectomy was performed and left renal pedicles were dissected without clamping and the entire left kidney was excised after 6 h. LA pretreatment was started 30 min prior to induction of ischemia. Injury to tubules was evaluated using light and electron microscopy. The expressions of MMP-2 and MMP-9 were determined by immunohistochemistry and their activities were analyzed by gelatin zymography. Serum creatinine was measured using a quantitative kit based on the Jaffe colorimetric technique. Malondialdehyde (MDA) and glutathione (GSH) were analyzed using high performance liquid chromatography. Tissue inhibitor of metalloproteinase (TIMP)-2 and TIMP-1 were assessed using enzyme-linked immunosorbent assay (ELISA). I-R caused tubular dilatation and brush border loss. LA decreased both renal dysfunction and abnormal levels of MDA and GSH during I-R. Moreover, LA decreased significantly both MMP-2 and MMP-9 expressions and activations during I-R. TIMP-1 and TIMP-2 levels were increased significantly by LA administration. LA modulated increased MMP-2 and MMP-9 activities and decreased TIMP-1 and TIMP-2 levels during renal I-R.